2010
DOI: 10.1123/jsep.32.3.339
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Imagery to Manipulate Challenge and Threat Appraisal States in Athletes

Abstract: The present study investigated whether imagery could manipulate athletes' appraisal of stress-evoking situations (i.e., challenge or threat) and whether psychological and cardiovascular responses and interpretations varied according to cognitive appraisal of three imagery scripts: challenge, neutral, and threat. Twenty athletes (M age = 20.85; SD = 1.76; 10 female, 10 male) imaged each script while heart rate, stroke volume, and cardiac output were obtained using Doppler echocardiography. State anxiety and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
91
11
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(115 citation statements)
references
References 32 publications
12
91
11
1
Order By: Relevance
“…For example, Williams, Cumming, and Balanos (2010) were unable to find consistent differences in cardiac output between participants when using challenge or threat imagery about a sport competition. The challenge imagery script was related to higher levels of self-efficacy compared to the threat script, providing some support for the cognitive component of the TCTSA.…”
Section: Challenge and Threat States In Athletesmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, Williams, Cumming, and Balanos (2010) were unable to find consistent differences in cardiac output between participants when using challenge or threat imagery about a sport competition. The challenge imagery script was related to higher levels of self-efficacy compared to the threat script, providing some support for the cognitive component of the TCTSA.…”
Section: Challenge and Threat States In Athletesmentioning
confidence: 96%
“…Collectively, both theory (Jones, 1995) and research (Hanton, Neil, & Mellalieu, 2008), suggest that in combination, a high perception of control and self-efficacy should, typically, be associated with emotional responses being perceived as helpful to performance regardless of the valence of the emotion. For example, Williams et al (2010) found that anxiety experienced during a challenge script was perceived as more helpful for performance. Moore, Vine, Wilson, and Freeman (2012) manipulated challenge and threat states by giving participants different monetary incentives and found that the challenge group reported a more facilitative interpretation of cognitive anxiety.…”
Section: Challenge and Threat States In Athletesmentioning
confidence: 99%
“…Layering can also incorporate Lang's (1979) bio-informational theory, whereby the first layer could be made up of stimulus propositions, with response and meaning propositions added in subsequent layers (e.g. Cumming, Olphin, & Law, 2007;Williams, Cumming, & Balanos, 2010). Imagery ability has been found to significantly increase following an intervention where a layering technique is used (Calmels et al, 2004).…”
Section: Sj Cooley Et Al: Methodological Variations In Guided Imagmentioning
confidence: 99%
“…Thus, the psycho-neuro-muscular theory asserts that vivid imagined events produce innervations in our muscles similar to that produced by the actual physical execution of the event. Coaches and athletes should know that mental imagery strengthens their muscle memories by having the muscle respond in the correct sequence without actually executing the movement, (Williams & al., 2010).…”
Section: Psycho-neuro-muscular Theorymentioning
confidence: 99%